The contributions of information and media literacy to public hybrid libraries - Ottonicar, Selma Leticia Capinzaiki [UNESP]; da Silva, Rafaela Carolina [UNESP]; Barboza, Elder Lopes [UNESP] (University of Chicago Press, 2018)
Standards and indicators of information and media literacy help individuals to evolve with public hybrid libraries. Regina Belluzzo promoted those standards to evaluate both information literacy and media literacy in Brazil. The purpose of this article is to demonstrate the relationship between standards and indicators of information literacy, media literacy, and services provided by public hybrid libraries in Brazil and Britain. The method is based on a literature review, which results in a table that relates each standard or indicator with services offered by information professionals and with users’ behavior. The study concludes that information and media literacy are important instruments for public hybrid libraries because they guide organizations’ goals, which contribute to education. From this perspective, hybrid libraries must be one potential form of libraries in the development of their communities.